Investigation characteristics of prosopis juliflora biodiesel blended with diesel fuel in a DI diesel engine. Issue 3 (27th May 2022) - Sasikumar, R.; Sankaranarayanan, G.; Karthikeyan, R.
ABSTRACT: The main aim of the work is to performance and emission of Prosopis Juliflora oil blended with Diesel fuel in a diesel engine. To extract the oil from the Prosopis Juliflora. oil through mechanical extraction. Property studies were made on the oil called PJFO, PJFO50D50 and PJFO40D50DEE10 to property characterise it as fuel for diesel engines. Blending of PJFO (namely PJFO50D50 and PJFO40D50DEE10) was prepared by mixing, respectively, diesel by volume. All the fuels were tested in a single cylinder diesel engine for their performance was compared to diesel fuel. Engine test results showed comparable performance for all PJFO50D50 and PJFO40D50DEE10with diesel fuel. At the full load condition, the power output the brake thermal efficiency was found as 31.43%, respectively, with PJFO40D50DEE10 and whereas it was 29.5% with BD. There is a considerable reduction in Smoke and NOx emissions with PJFO40D50DEE10 compared to BD at all power outputs. Abbreviations : PJFO: Prosopis juliflora oil; BP: Brake Power; BTE: Brake Thermal Efficiency; SFC: Specific Fuel Consumption; EGT: Exhaust Gas Temperature; NOX : Nitrogen oxide; HC: Hydrocarbon; CO: Carbon Mono Oxide